Quality of life among dialysis patients: predictive analysis of illness intrusiveness and spiritual beliefs - Kehkashan Arouj; Rabia Zonash Mir; Seema Zahid (Journal of the Pakistan Medical Association, 2022)
Objectives: To investigate the predicting effect of illness intrusiveness and spiritual belief determining dialysis patients’ quality of life. Method: The correlational study was conducted from September 2018 to July 2019 in Rawalpindi and Islamabad, Pakistan, and comprised adult patients of either gender experiencing dialysis issues for one year at the Pakistan Institute of Medical Sciences, the Pakistan Kidney Patients Association, the Islamabad Dialysis and Nephro Care Centre, the Bahria International Hospital and the Shifa Hospital Kidney Centre. Data was collected using the Illness Intrusiveness Scale, the Daily Spiritual Experience Scale, the World Health Organisation Quality of Life Scale, and a demographic sheet. Data was analysed using SPSS 23. Results: Out of 200 patients, 116(58%) were males and 84(42%) were females. Female patients had higher mean values for illness intrusiveness value 62.08±14.47, spiritual belief 33.45±14.75 psychological health 18.00±3.88 and environmental health 25.15±4.93. Male dialysis patients had higher mean values for physical health 19.11±7.51 and social relationship 10.50±2.45. Illness intrusiveness was a significant negative predictor of physical health (p<0.000), psychological health (p<0.001), social relationship (p<0.000) and environmental health (p<0.05). Spiritual belief was a significant positive predictor of physical health (p<0.01), psychological health (p<0.001), social relationship (p<0.05) and environmental health (p<0.05). Conclusion: High level of illness intrusiveness in dialysis patients tended to decrease life quality. Those having a higher level of spiritual belief tended to develop a better approach to life quality. Key Words: Illness intrusiveness, Spiritual beliefs, Physical health, Psychological health, Social relationship, Environmental health, Dialysis patients.